The Compliance of Independent Practice Midwife (PMB) in Completing the MCH Handbook In Lamongan Regency, East Java - Sulistiyowati, Sulistiyowati; Khoiriyah, Ansih (Universitas Islam Lamongan, 2020)
The government makes a policy for health workers to use MCH Handbook as a communication tool and medium for counseling mothers, families and the community regarding maternal and child health services including their references, mother and child service packages, nutrition, immunization and toddler development. The purpose of this study is to determine the factors that influence the compliance of MCH Handbook completion. This research is an analytic study with cross sectional approach. The population in the study were all Independent Midwife Practices (PMB) in the Lamongan district area which were listed in the IBI Branch Management as many as 572, which were divided into 38 branches. The samples were 82 PMB obtained through simple random sampling, namely the lottery technique. The independent variables in this study were Knowledge, Motivation, Supervision and Work Time while the dependent variable is Compliance with the MCH Handbook. The collected data were processed using Bivariate and Multivariate tests. The results showed that the variables of knowledge, motivation, supervision and length of work affected the compliance of midwives in completing the MCH handbook with p <0.05. It means that H0 was rejected and H1 was accepted. The effects were also influenced the knowledge variable where p <0.05. Based on the above data, it can be concluded that completing the MCH Handbook by midwives is important in order to monitor the development of maternal and infant health and as a means of communication to the patients. Keywords: Compliance, Midwife, Mother and Child Handbook